Comparison of the lyrics paradoxically Sanai and Attar - مرتضی محسنی; سیاوش حق جو; عفت سادات غفوری (مطالعات زبانی و بلاغی)
Paradoxes in poetry, both in language and the meaning domains bring about defamiliarization and bumps. This technique has long been considered by poets and factors such as evolutionary development of literature from simplicity into intricacy and the combination of mysticism with Persian literature played a role in its emergence and spread. Paradoxical elements are being applied in the form of combination or paradoxical image and sentence or expression used by paradox In this article in addition to defining paradox and its history and the fields of its emergence …a comparison had been made between different kinds of paradoxes and their substrates in the fields of semantic and aesthetic and in two interpretative and composite   structures in the   collection   of lyrics by two mystical poet Attar, Sanai. Although the paradox of images and poems begins by Sanai an his lyrical poetry; so its growing trend must be deliberated in the Attar lyrics and the graph results indicates that in   paradoxical interpretations both in aesthetic and conceptual fields we are faced with the frequency range of 15 to 20 percent compared to the Sanai lyrics; While it can be seen almost equally a small percentage of paradox in the collection of the lyrics of two poets. This two mystic poets who seek to express mystical concepts and ideas had a tendency towards interpretations. Interpretations accompanied by concepts which cause to ……..and guide his accustomed and away from the truth mind to the truth